2000
DOI: 10.1002/(sici)1098-2744(200005)28:1<31::aid-mc5>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

The role of wild-type and mutated N-ras in the malignant transformation of liver cells

Abstract: In order to determine the role of N-ras overexpression and mutation in malignant liver cell transformation, wild-type and mutated N-ras were transfected into the rat liver epithelial cell line OC/CDE 22, and N-ras expression, growth kinetics, growth in soft agar, and tumorigenicity in vivo as well as the involvement of the mitogen-activated protein kinase (MAPK) signal transduction pathway in the expression of the malignant phenotype were analyzed. Although OC/CDE 22 cells transfected with wild-type N-ras show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…NRAS appears to cooperate with Arf deficiency to promote tumorigenesis in the liver. This is consistent with previous work demonstrating cooperation of the Arf and ras pathways in cellular transformation (34) and the ability of NRAS to transform a nontumorigenic liver epithelial cell line (35). Interestingly, NRAS combined with a heterozygous Arf mutation was sufficient to promote tumorigenesis in this model without observable loss of heterozygosity, although at a much-reduced penetrance.…”
Section: Discussionsupporting
confidence: 92%
“…NRAS appears to cooperate with Arf deficiency to promote tumorigenesis in the liver. This is consistent with previous work demonstrating cooperation of the Arf and ras pathways in cellular transformation (34) and the ability of NRAS to transform a nontumorigenic liver epithelial cell line (35). Interestingly, NRAS combined with a heterozygous Arf mutation was sufficient to promote tumorigenesis in this model without observable loss of heterozygosity, although at a much-reduced penetrance.…”
Section: Discussionsupporting
confidence: 92%
“…Since all BRAF mutations to date have been reported to occur in exons 11 and 15 (Brose et al, 2002;Davies et al, 2002;Naoki et al, 2002;Yuen et al, 2002), each line was screened for variants in these exons by PCR sequencing. NRAS was also screened for mutations in codons 12, 13 and 61, which have been found previously to activate the potential of NRAS to transform cultured cells (Schleger et al, 2000) and have been found in a variety of human tumors including melanomas (van Elsas et al, 1996). For further information refer to Supporting Text 2.…”
Section: Genotyping Of Cell Linesmentioning
confidence: 99%
“…The F344 rat rarely develops sporadic liver tumors, so this high MF level raises the question regarding the role of K-ras mutations in the carcinogenic process in rat liver. K-ras mutations may cause a cellular functional change of increased and continuous MAPK pathway activation, which may be a necessary, but not rate-limiting, part of the carcinogenic process (24). Tumor development and carcinogenesis is a complex process in which polyclonal interactions may be a major contributor to overall growth and selection advantage.…”
Section: Discussionmentioning
confidence: 99%